AGS 104 -- A New Rye Cultivar for Winter Forage and Silage Production - Ann Blount; Ronald Barnett; Jerry Johnson; Chery Mackowiak; Yoana Newman (EDIS, 2007)
SS-AGR-278, a 2-page fact sheet by Ann Blount, Ronald Barnett, Jerry Johnson, Cheryl Mackowiak, and Yoana Newman, describes this rye cultivar, developed for early season forage production. Published by the UF Department of Agronomy, October 2007.